2006
DOI: 10.1017/s0022112006000371
|View full text |Cite
|
Sign up to set email alerts
|

Breaking symmetries in induced-charge electro-osmosis and electrophoresis

Abstract: Building on our recent work on induced-charge electro-osmosis (ICEO) and electrophoresis (ICEP), as well as the Russian literature on spherical metal colloids, we examine the rich consequences of broken geometric and field symmetries upon the ICEO flow around conducting bodies. Through a variety of paradigmatic examples involving ideally polarizable (e.g. metal) bodies with thin double layers in weak fields, we demonstrate that spatial asymmetry generally leads to a net pumping of fluid past the body by ICEO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
389
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 323 publications
(407 citation statements)
references
References 62 publications
17
389
1
Order By: Relevance
“…This unusual phenomenon, which cannot be attributed to DEP, is the first experimental observation of an effect predicted theoretically by Squires and Bazant [7], although we find important differences as well. Using the standard low-voltage model for thin double layers, Squires and Bazant predicted that a metallic sphere with a hemispherical dielectric coating oriented perpendicular to the field will move by ICEP in the direction of its dielectric end at a velocity,…”
supporting
confidence: 71%
See 3 more Smart Citations
“…This unusual phenomenon, which cannot be attributed to DEP, is the first experimental observation of an effect predicted theoretically by Squires and Bazant [7], although we find important differences as well. Using the standard low-voltage model for thin double layers, Squires and Bazant predicted that a metallic sphere with a hemispherical dielectric coating oriented perpendicular to the field will move by ICEP in the direction of its dielectric end at a velocity,…”
supporting
confidence: 71%
“…Bazant and Squires [3,4] conceptually unified this phenomenon with AC electro-osmosis at electrodes, first described by Ramos et al [5] and Ajdari [6], and suggested the term "induced-charge electro-osmosis" (ICEO) to describe all flows resulting from the action of an applied electric field on its own induced diffuse charge near a polarizable surface. They also predicted how broken symmetries could cause polarizable particles to move in electric fields by "induced-charge electrophoresis" (ICEP) [3,7]. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The nonlinear electrokinetic response was described for particles in an isotropic fluid, first by Murtsovkin et al [178][179][180][181] , and then analysed systematically by Bazant and Squires [182][183][184][185][186] , who predicted that asymmetric particles can show a quadratic dependence of the electrophoretic velocity on the applied electric field, in the so-called induced charge electrophoresis (ICEP).…”
Section: Liquid Crystal Enabled Electrophoresismentioning
confidence: 99%